An alternative technique to safely close the chest after placing a child on central venoarterial extracorporeal membrane oxygenation. Issue 5 (29th March 2017) - Bobos, Dimitrios; Kanakis, Meletios A.; Koulouri, Sofia; Rammos, Spyridon; Karabinis, Andreas; Giannopoulos, Nicholas M.
Key Clinical Message: Central venoarterial (VA) placement of extracorporeal membrane oxygenation (ECMO) is performed surgically, and in the majority of cases, the patient remains with an open sternum. Herein, a case of a 3‐year‐old patient who underwent insertion of a central VA ECMO for heart failure due to acute myocarditis is described. An alternative technique for ECMO placement providing sternal closure and minimizing infection risk for the safe patient transport is described. Abstract : Central venoarterial (VA) placement of extracorporeal membrane oxygenation (ECMO) is performed surgically, and in the majority of cases, the patient remains with an open sternum. Herein, a case of a 3‐year‐old patient who underwent insertion of a central VA ECMO for heart failure due to acute myocarditis is described. An alternative technique for ECMO placement providing sternal closure and minimizing infection risk for the safe patient transport is described.